Exergy analysis of a diesel engine converted to spark ignition operating with diesel, ethanol, and gasoline/ethanol blends. (December 2020) - Zapata-Mina, Juan; Restrepo, Alvaro; Romero, Carlos; Quintero, Hector
Highlights: Experimental and exergy analysis on a diesel engine converted to spark ignition. Effect of ethanol and blends with gasoline on a diesel engine was evaluated. Tests were performed regarding variable compression ratio and varied engine speeds. Experimental tests showed a better performance by becoming to spark ignition. The compression ratio favored ethanol when operating at high rotational speeds. Abstract: Biofuels such as ethanol have been used in internal combustion engines to reduce polluting emissions. However, some studies show that they affect engine performance due to their differences in thermophysical properties. Besides, pure ethanol has not been properly evaluated in compression ignition engines. Therefore, this work shows the results of an exergy analysis in a single cylinder compression ignition engine converted to spark ignition engine of varying compression ratio, operated with diesel, ethanol, and gasoline/ethanol blends, in different operating parameters. Tests were carried out on the engine without modifications operating diesel at a compression ratio of 17:1 and converted to spark ignition with 50%, 10% gasoline/ethanol blends and pure ethanol at compression ratios of 9:1, 12:1 at rotation speeds of 1500, 2100, 2600 and 3200 rpm. Under the experimental operating conditions, the results of the modified engine showed that the blend 50% and ethanol performs better by operating with 12:1 compression ratio, in relation to exergetic efficiency and environmental effect factor. Besides, the engine showed a better performance by becoming to spark ignition operating with ethanol and gasoline/ethanol blends.